2021
DOI: 10.1136/annrheumdis-2021-220097
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and treatment retention of TNF inhibitors when used as monotherapy versus comedication with csDMARDs in 15 332 patients with psoriatic arthritis. Data from the EuroSpA collaboration

Abstract: BackgroundComedication with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) during treatment with tumour necrosis factor inhibitors (TNFi) is extensively used in psoriatic arthritis (PsA), although the additive benefit remains unclear. We aimed to compare treatment outcomes in patients with PsA treated with TNFi and csDMARD comedication versus TNFi monotherapy.MethodsPatients with PsA from 13 European countries who initiated a first TNFi in 2006–2017 were included. Country-specific comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…Although persistence rates reported in the literature vary widely depending on the study and definition used, we found 1-year rates for biologics similar to those reported previously. Specifically, the previous 1-year rates of TNF inhibitor persistence ranged from 65% to 79% for PsO and from 56% to 90% for PsA . The corresponding values in the present study were 73.8% and 72.3%, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…Although persistence rates reported in the literature vary widely depending on the study and definition used, we found 1-year rates for biologics similar to those reported previously. Specifically, the previous 1-year rates of TNF inhibitor persistence ranged from 65% to 79% for PsO and from 56% to 90% for PsA . The corresponding values in the present study were 73.8% and 72.3%, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…A striking fact of our study was the predictive capacity of previous exposure to methotrexate in terms of lower persistence of IXE. These data are especially curious if we consider that the concomitant use of methotrexate tends to prolong the survival of TNFi in PsA [ 16 ]. The hypothesis put forward in these studies is that methotrexate would reduce the immunogenicity against TNFi, allowing a higher survival of these drugs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are especially curious if we consider that the concomitant use of methotrexate tends to prolong the survival of TNFi in PsA [ 16 ]. The hypothesis put forward in these studies is that methotrexate would reduce the immunogenicity against TNFi, allowing a higher survival of these drugs [ 16 ]. However, clinical trials with IXE show that the associated use of methotrexate has no role in either the therapeutic response or the persistence of the drug [ 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…В то же время в наблюдательном исследовании U. Lindström и соавт. [13] на большой выборке пациентов с ПсА (более 15 332 человек) показано, что терапия иФНО-α АДА и инфликсимабом в комбинации с МТ на 50% повышает вероятность достижения ремиссии по DAS28 в течение 1 года лечения по сравнению с монотерапией иФНО-α.…”
Section: Discussionunclassified